IMPLEMENTASI DAN EFEKTIFITAS STRATEGI KEPEMIMPINAN TERHADAP KUALITAS DAN PRESTASI KINERJA KARYAWAN - khoirudin, muhammadadi_ (MIZANIA: Jurnal Ekonomi Dan Akuntansi, 2021)
One of the most important factors in the success of a company is the involvement of its employees. It is impossible to separate out the fact that a company's strategy and efforts to link leadership styles are informed by many other factors. The decrease in employee performance evaluation results and the decrease in productivity of the sphygmomanometer both indicate low employee performance (blood pressure). Employees play an important role in the success of the company because they are the managers of the system and are one of the most important factors in the success of the company. Organizational culture and leadership style are used as a means to increase employee productivity. Leadership style is one of the ways that companies use to motivate their employees, and if they don't get a good leadership style, they will not be able to achieve their goals. Leaders and employees can work together to achieve the desired leadership style. Therefore, the company must be able to improve a rule that can increase employee motivation, with established rules, with good rules and leadership styles. Thus, Employees are expected to follow company policies and not be involved in extracurricular activities. so that the presence of a leadership style can help motivate them to do their best work. Keywords: Quality of Employee, Performance Leadership Style, Implementation